Use and Acceptance of Electronic Communication by Patients With Multiple Sclerosis: A Multicenter Questionnaire Study - Haase, Rocco; Schultheiss, Thorsten; Kempcke, Raimar; Thomas, Katja; Ziemssen, Tjalf (JMIR Publications, 2012)
BackgroundThe number of multiple sclerosis (MS) information websites, online communities, and Web-based health education programs has been increasing. However, MS patients' willingness to use new ways of communication, such as websites, mobile phone application, short message service, or email with their physician, remains unknown. ObjectivesWe designed a questionnaire to evaluate the a priori use of electronic communication methods by MS patients and to assess their acceptance of such tools for communication with their health care providers. MethodsWe received complete data from 586 MS patients aged between 17 and 73 years. Respondents were surveyed in outpatient clinics across Germany using a novel paper-and-pencil questionnaire. In addition to demographics, the survey items queried frequency of use of, familiarity with, and comfort with using computers, websites, email, and mobile phones. ResultsAbout 90% of all MS patients used a personal computer (534/586) and the Internet (527/586) at least once a week, 87.0% (510/586) communicated by email, and 85.6% (488/570) communicated by mobile phone. When asked about their comfort with using electronic communication methods for communication with health care providers, 20.5% (120/586) accepted communication by mobile Internet application or short message service via mobile phone, 41.0% (240/586) by websites, 54.3% (318/586) by email service, and 67.8% (397/586) by at least one type of electronic communication. The level of a priori use was the best predictor for the acceptance of electronic communication with health care providers. Patients who reported already searching online for health information (odds ratio 2.4, P < .001) and who had already communicated with a physician through a website (odds ratio 3.3, P = .03) reported higher acceptance for Web-based communication. Patients who already scheduled appointments with their mobile phones (odds ratio 2.1, P = .002) were more likely to accept the use of mobile phone applications or short message service for communicating with their physician. ConclusionsThe majority of MS patients seen at specialist centers already use modern communication technology regularly. New forms of electronic communication appear to have high levels of acceptance for exchanging information about MS between patients and health care providers. Such methods should be integrated into eHealth services such as electronic health records and patient relationship management systems.